Business Process Modelling is an Essential Part of a Requirements Analysis - de Lusignan, S.; Krause, P.; Michalakidis, G.; Vicente, M. Tristan; Thompson, S.; McGilchrist, M.; Sullivan, F.; van Royen, P.; Agreus, L.; Desombre, T.; Taweel, A.; Delaney, B. (Yearbook of Medical Informatics, 2012)
To perform a requirements analysis of the barriers to conducting research linking of primary care, genetic and cancer data.We extended our initial data-centric approach to include socio-culturalandbusinessrequirements.Wecreatedreferencemodels of core data requirements common to most studies using unified modelling language (UML), dataflow diagrams (DFD) and business process modelling notation (BPMN). We conducted a stakeholder analysis and constructed DFD and UML diagrams for use cases based on simulated research studies. We used research output as a sensitivity analysis.Differences between the reference model and use cases identified study specific data requirements. The stakeholder analysis identified: tensions, changes in specification, some indifference from data providers and enthusiastic informaticians urging inclusion of socio-cultural context. We identified requirements to collect information at three levels: microdata items, which need to be semantically interoperable, meso-the medical record and data extraction, and macro-the health system and socio-cultural issues. BPMN clarified complex business requirements among data providers and vendors; and additional geographical requirements for patients to be represented in both linked datasets. High quality research output was the norm for most repositories.Reference models provide high-level schemata of the core data requirements. However, business requirements’ modelling identifies stakeholder issues and identifies what needs to be addressed to enable participation.
Keywords: General practice; medical records systems; computerized; research design; registry; records as topic